Analysis on the demand and influencing factors of virtual simulation training for Traditional Chinese Medicine nursing technology (中医护理技术虚拟仿真培训需求现状及影响因素分析) - CHEN Yumei (陈玉梅); ZHANG Gai (张改); LI Shufang (李淑芳); KANG Yuwen (康玉闻); LI Qingwei (黎庆卫) (Association of Integrative Nursing, 2021)
Objective To explore the current status of nursing staff's demand for virtual simulation training of Traditional Chinese Medicine (TCM) nursing technology, and analyze its influencing factors, in order to lay a theoretical foundation for the targeted development and application of TCM nursing simulation training system. Methods From July to October 2019, 320 nursing staff from three tertiary first-class TCM hospitals in Guangdong Province were selected. The general information questionnaire designed by the researcher and the nursing staff were used to investigate the technical needs of TCM nursing. Status of nursing simulation training needs and its influencing factors were analyzed. Results Acupuncture, moxibustion and cupping were the three most important needs of nursing staff for virtual simulation technology training, and the demand levels were (90. 26 ± 3. 14) points, (89. 23 ± 2. 08) points, and (87. 29 ± 3. 68) points, respectively. Multi-factor analysis shows that working department, working years, and whether you have any knowledge of virtual simulation are factors that affect the training needs of nursing staff in traditional Chinese medicine virtual simulation technology. Conclusion Nursing staff had a high degree of demand for virtual simulation. High-risk nursing projects such as acupuncture, moxibustion, cupping can be used as the first priority for the development of a virtual simulation system for TCM nursing. Young medical nurses can be used as the first pilot of this system The personnel will help the system to exert the best training effect. (目的 探讨护理人员对中医护理技术虚拟仿真培训的需求现状, 并分析其影响因素, 为中医护理技术虚拟仿真培训系统的针对性开发及应用提供参考。方法 2019年7月-10月, 选取广东省3家三级甲等中医院320名护理人员, 采用研究者自行设计的一般资料调查表及护理人员对中医护理技术需求问卷进行调查, 分析护理人员对中医护理技术虚拟仿真培训需求的现状及其影响因素。结果 护理人员对虚拟仿真技术培训需求程度居前3位的分别为针刺、艾灸、拔火罐, 需求程度分别为(90. 26±3. 14)分、(89. 23±2. 08)分、(87. 29±3. 68)分。多因素分析显示, 工作科室、工作年限、有无了解过虚拟仿真为影响护理人员中医虚拟仿真技术培训需求的因素。结论 护理人员对虚拟仿真的需求程度整体较高, 针刺、艾灸、拔火罐等高风险护理项目可作为中医护理虚拟仿真系统开发的首优项目, 内科青年护理人员可作为此系统的首批试点人员, 将有利于该系统发挥最佳培训效果。)